2010
DOI: 10.2146/ajhp080188
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled morphine for palliation of dyspnea in end-stage cystic fibrosis

Abstract: Inhaled morphine was effective in relieving dyspnea in a patient with end-stage CF lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Opiates and inhaled anaesthetic agents decrease the perceptual responses and thus lessen the intensity of respiratory sensation (Hayes 2010;Jennings 2002). The exact mechanism by which opioids alleviate breathlessness is still not known.…”
Section: How the Intervention Might Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Opiates and inhaled anaesthetic agents decrease the perceptual responses and thus lessen the intensity of respiratory sensation (Hayes 2010;Jennings 2002). The exact mechanism by which opioids alleviate breathlessness is still not known.…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…The review found that there is lack of studies discussing palliative drug treatments for breathlessness in people with CF. The available literature is in the form of case studies, which need to be assessed when making clinical decisions (Cohen 2002;Gra 2004;Hayes 2010;Janahi 2000). The excluded study was cross-over in design and compared hydrocodone to placebo (Browning 1988).…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%
“…The later stages of CF are inundated with frequent hospitalizations. Treatment during end-stage CF is palliative rather than curative (Lowton & Gabe, 2003), and without lung transplantation, CF remains a fatal disease due to respiratory failure (Hayes, Anstead, Warner, Kuhn, & Ballard, 2010). Nevertheless, medical breakthroughs have increased the survival rate of children with CF (Blum, 1992) and now many children are living into adulthood.…”
mentioning
confidence: 99%